RASIONALISASI DAN REALITAS BUDAYA JAWA TERHADAP MOTIF GURDA - Sudarwanto, Aan (Institut Seni Indoensia Surakarta, 2018)
The article that discusses the motive of the gurda aims to find out more clearly how the position and changes in the gurda motives in the perspective of Javanese society. In addition, it is also to find out the forms of the gurda motif and its application to Javanese culture from several perspectives, namely tradition, modern and postmodern.Changes from tradition to modernism then arrive at postmodern discourse to be interesting, because from there it can be analyzed how far the changes are from aspects of form, structure and application, as well as several causes. Several approaches are used in analyzing these problems. among others, using the concept of Max Weber's rationality and the concept of deconstruction that Derrida proposes.The importance of material objects raised in this article is based on the idea that the gurda motif on batik does not appear suddenly but has undergone a very long journey. The motif that symbolizes the eagle was originally described as more realistic and even anthropomorphic which can be found in various temple realiefs on Java, including Prambanan temple, Penataran temple, jago temple, candi Belahan and Sukuh temple. After becoming a batik motif until the postmodern era also experienced a very interesting dynamic to study so that it could become a model of changing a cultural phenomenon.Â Keywords: motifs of gurda, tradition, modern, postmodern discourse